Digestive manifestations in hospitalized patients with COVID-19 - Cesar Abrahan Aguero Figueredo; Moyra Agüero Figueredo; Yenier López Barrero; Lilian Zúñiga Fernández (Revista Cubana de Medicina Militar, 2022)
Introduction: COVID-19 has caused an unprecedented health crisis, as it is an emerging, unprecedented disease with high transmissibility. New different strains from the original variant of the virus have already been identified, which could mean a change in its clinical presentation patterns. Objective: To describe the digestive manifestations in patients hospitalized due to COVID-19. Methods: A descriptive, prospective study was carried out in patients diagnosed with COVID-19, admitted among the months of July and September 2021; 136 patients were studied. Each selected patient had the individual medical record compiled. The variables taken into consideration were sex, age, comorbidities, presence of digestive manifestations and duration of digestive symptoms. The average and standard deviation for the duration of the digestive symptoms were calculated, and in the remaining variables, the results were expressed in absolute frequency and percentages. Results: Digestive manifestations were present in 58,8 % of the patients. Diarrhea occurred in 29,4 %, a with an average duration of approximately 1,9 days, and was the earliest digestive symptom of all those identified. Nausea and anorexia occurred in 25 %; anorexia was the symptom that lasted the longest, with a maximum of 10 days. Conclusions: The digestive manifestations in hospitalized patients with COVID-19 were diarrhea, nausea, vomiting, epigastric pain, anorexia and dyspepsia, of which the most frequent presentation was: diarrhea, nausea and anorexia.